PENGARUH KOMBINASI TWEEN 80 DAN SPAN 80 SEBAGAI EMULSIFIER PADA ENKAPSULASI EKSTRAK BUNGA KENIKIR MENGGUNAKAN ENKAPSULAN MALTODEKSTRIN - Sukarno, Gusti Ayu Gayatri Amasdenia; Wartini, N. M.; Arnata, I W. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 4 (2022): DesemberDO - 10.24843/JRMA.2022.v10.i04.p06, 2022)
This study aims to determine the effect of tween 80 and span 80 combination on the characteristics of the kenikir flower dye extract encapsulate and determine the best combination of tween 80 and span 80 to produce kenikir flower dye extract encapsulates. This study is a one-factor experiment using a simple randomized block design with a combination treatment of tween 80 (T) with span 80 (S), to achieve HLB values ??of 8, 9, 10, 11, 12 and 13. Each treatment was carried out three  times to get 18 units. The data obtained were analyzed by analysis of variance and if treatment affects  the observed variables, it was continued with Duncan's Test. The results showed that the combination of tween 80 and span 80 as an emulsifier affected the water content, total carotenoids, surface carotenoids, encapsulation efficiency, brightness level, redness level and yellowness level and had no effect on the yield and solubility of the encapsulated extract of kenikir flower dye extract. Based on the  effectiveness index, the combination of HLB 9 (Twen 80 0.18g and Span 80 0.32g) was the best combination to produce an encapsulate of kenikir flower dye extract with the characteristics of 78.54% yield, 5.57% water content, 90.43% solubility, total carotenoids. 27.59%, surface carotenoids 0.64%, encapsulation efficiency 97.70% with brightness (L*) 35.92, redness (a*) 24.23 and yellowness (b*) 32.48.